Clinical Spectrum and Outcomes of Paediatric Status Epilepticus - Madeeha Aimen, Muhammad Hassan Tahir, Farooq Tariq, Nazia Mehmood, Sobia Naeem, Anum Fatima, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To assess the clinical spectrum, etiological, and outcome of paediatric status epilepticus (SE) in patients with children who present to a tertiary care hospital. Place and Duration of Study: The study was a cross-sectional observation study which was carried out in Paediatric Department of Mayo Hospital, Lahore from October 2022 to April 2023. Methodology: The sample size was calculated with the help of WHO sample size calculator. Non-probability consecutive sampling involved a total of 150 patients with status epilepticus of 1 month to 12 years of age. Status epilepticus was seizure that lasted over five minutes or recurrent seizures without consciousness in between the incidents. Comprehensive history, physical examination, and topography lab and radiography were conducted to identify the underlying etiology. The patients were treated in line with the standard treatment procedures. They measured the outcomes based on recovery, neurological deficits, and mortality during hospital stay. Results: Out of 150 patients, 88 (58.7) were males and 62 (41.3) were females. The age group that was most impacted was the 15 years or younger (46%). Most common was the generalized tonic-clonic seizures (72%). The most common ones were febrile seizures (34 percent), central nervous system infections (26 percent), epilepsy (20 percent), and metabolic disturbances (12 percent). There was full recovery in 102 (68) and 30 (20) patients who had neurological complications. Deaths were noted in 18 (12%) patients with mostly infectious causes. Conclusion: Paediatric status epilepticus is a serious neurological emergency having various clinical manifestations and having high morbidity and mortality. Early diagnosis, prompt treatment and detection of causative factors are necessary to enhance the outcome and minimize complications in affected children. Keywords: Paediatric status epilepticus, Seizures, Febrile seizures, Central nervous system infections, Epilepsy, Neurological outcomes, Mortality.